Clinical efficacy of casirivimab-imdevimab antibody combination treatment in patients with COVID-19 Delta variant. Issue 9 (September 2022) - Miyashita, Naoyuki; Nakamori, Yasushi; Ogata, Makoto; Fukuda, Naoki; Yamura, Akihisa; Ishiura, Yoshihisa
Abstract: Introduction: Casirivimab-imdevimab, an antibody cocktail containing two severe acute respiratory syndrome coronavirus 2 neutralizing antibodies, reduces the viral load and the risk of coronavirus disease 2019 (COVID-19)-related hospitalization or death. The objective of this study was to evaluate the clinical efficacy of casirivimab-imdevimab in patients with COVID-19 Delta variant in Japan. Methods: This study was conducted at five institutions and assessed a total of 461 patients with COVID-19 who met the inclusion criteria. The treatment group received a dose of casirivimab-imdevimab consisting of a cocktail of two monoclonal antibodies, (casirivimab 600 mg and imdevimab 600 mg intravenously). The control consisted of age- and sex-matched COVID-19 patients (n = 461) who sufficed the inclusion criteria but did not receive casirivimab-imdevimab. The outcome was the requirement of oxygen therapy. Results: In the treatment group, patients received oxygen therapy (n = 30), nasal canula (n = 23), high flow nasal cannula (n = 5), and mechanical ventilation (n = 2). In the control group, patients received oxygen therapy (n = 56), nasal canula (n = 45), high flow nasal cannula (n = 8), and mechanical ventilation (n = 3). The administration of oxygen therapy was significantly lower in the treatment group than the control group (6.5% vs. 12.1%, P = 0.0044). All these patients admitted to our hospitals and received additional therapy and recovered. Conclusions: Our results demonstrate that the casirivimab-imdevimab combination antibody treatment is associated with reduced rates of requiring oxygen therapy among high-risk patients with COVID-19 Delta variant.